Experience of a Preventive Experiment: Spatial Social Mixing in Post-World War II Housing Estates in Helsinki, Finland. - Vaattovaara, Mari; Joutsiniemi, Anssi; Kortteinen, Matti; Stjernberg, Mats; Kemppainen, Teemu (Springer Open, 2018)
The contingent of large housing estates built in the 1960s and 1970s accounts for almost a half of all high-rises in Finland. The primary ideology in their genesis was to combine industrially prefabricated urban housing development with the surrounding forest landscape - together with a policy of spatial social mixing - to prevent social disorder and segregation. These policies seemed to work as intended until the early 1990s, but have since proved to be insufficient. With Western integration and new information and communication-based economic growth, new trends of population differentiation have emerged. As new wealth has moved out to the fringes of cities, the large housing estates have declined socio-economically - and have been enriched ethnically. This differentiation is structurally produced, works through the regional housing market and, as such, is beyond the scope of the preventive policies pursued. Recent attempts at controlling the regional markets and new forms of spatial social mixing have so far proved difficult.
Keywords: Wohnungswesen; Wohnsiedlung; Wohnumfeld; Segregation; Prävention; Großwohnsiedlung; Soziale Mischung; Fallbeispiel